Discrepancy between leg and capillary blood flow kinetics during knee extension exercise - Schlup, Susanna J. (Kansas State University, 2013)
Previously in our laboratory, capillary blood flow (QCAP) kinetics were found to be significantly slower than femoral artery (QFA) kinetics following the onset of knee extension exercise. If the increase in QCAP does not follow a similar time course to QFA, blood must be flowing into the leg but not to the working muscle. One possible explanation for this discrepancy is that blood flow also increases to the nonworking lower leg muscles. Purpose: To determine if cuffing below the knee alters the kinetics of QFA and QCAP during knee extension exercise, and provide insight into the potential mechanisms controlling the rapid increase in QFA. Methods: Subjects performed a ramp max test to determine the work rate at which gas exchange threshold (GET) occurred. At least four constant work rate trials in each condition were conducted at work rates eliciting ~80% GET. Trials were performed with and without below knee occlusion. Pulmonary gas exchange, near-infrared spectroscopy, QFA and mean arterial pressure (MAP) measurements were taken. Muscle oxygen uptake (VO2m) and deoxy[hemoglobin + myoglobin] were used to estimate QCAP. Conductance (C) was calculated (QFA/MAP) and the percent change from baseline at 60s into exercise was calculated to indicate a time course of change. Results: There was no significant difference between the uncuffed and cuffed conditions (P>0.05). The mean response times (MRT) of QFA were 18.7 ± 14.2s (uncuffed) and 24.6 ± 14.9s (cuffed). QCAP MRTs were 51.8 ± 23.4s (uncuffed) and 56.7 ± 23.2s (cuffed), which were not significantly different from the time constants (τ) of VO2m (39.7 ± 23.2s (uncuffed) and 46.3 ± 24.1s (cuffed)). However, the MRT of QFA was significantly faster (P<0.05) than the MRT of QCAP and τVO2m. τVO2m and MRT QCAP were significantly correlated. The QFA and C percent increase from baseline at 60s were significantly different from MAP but not from each other. Conclusion: Cuffing below the knee did not significantly change the kinetics of QFA, QCAP or VO2m. Estimated QCAP kinetics tracked VO2m following exercise onset, while changes in QFA appeared to be primarily driven by an increase in C, not an increase in MAP.
Keywords: Knee extension exercise; Blood flow control; Blood flow kinetics; Kinesiology (0575); Physiology (0719)